Hereditary thrombocythemia caused by a thrombopoietin (THPO) gain-of-function mutation associated with multiple myeloma and congenital limb defects - Stockklausner, Clemens; Echner, Nicole; Klotter, Anne-Christine; Hegenbart, Ute; Dreger, Peter; Kulozik, Andreas (Annals of hematology, 2012)
Hereditary thrombocythemia (HT) has been described as a rare benign disorder caused by mutations in the thrombopoietin (THPO) or the c-Mpl receptor genes. Here we report two families with HT resulting from a THPO c.13+1 G>C mutation in the splice donor of intron 3. In one family there were coexisting distal limb defects, whereas in the other one member developed early-onset multiple myeloma. These observations, together with previously reported patients, suggest that THPO gain of function may dysregulate the hemangioblast and disturb vasculogenesis and hematopoietic development. Overstimulation of the THPO pathway might therefore predispose to clonal hematopoietic disease and to congenital abnormalities.
Gesehen am 28.08.2020